Genetic deletion of HVEM in a leukemia B cell line promotes a preferential increase of PD-1- stem cell-like T cells over PD-1+ T cells curbing tumor progression - del Rio, Maria-Luisa; de Juan, Carla Yago-Diez; Roncador, Giovanna; Caleiras, Eduardo; Álvarez-Esteban, Ramón; Pérez-Simón, José Antonio; Rodriguez-Barbosa, Jose-Ignacio (Frontiers in Immunology, 2023)
Abstract A high frequency of mutations affecting the gene encoding Herpes Virus Entry Mediator (HVEM, TNFRSF14) is a common clinical finding in a wide variety of human tumors and more often on those of hematological origin. We have addressed how HVEM expression on A20 leukemia cells influences tumor survival and its involvement in the modulation of the anti-tumor immune responses in a parental into F1 mouse tumor model of hybrid resistance. Exon 1 encoding the first part of the signal peptide of HVEM gene was targeted by CRISPR/Cas9 for the abrogation of protein expression. HVEM WT or HVEM KO leukemia cells were then injected intravenously into semiallogeneic F1 recipients and the extent of tumor dissemination was evaluated. The loss of HVEM expression on A20 leukemia cells led to a significant increase of lymphoid and myeloid tumor infiltration curbing tumor progression. A great diversity of lymphocyte populations was found significantly augmented in the infiltrates of metastatic lesions of HVEM KO tumors compared to those generated from HVEM WT tumors that display stem cell-like phenotypic features and molecular markers of exhaustion according to the combined expression of PD-1 and Tim3. Despite the accumulation co-inhibitory receptors and molecular features of exhaustion, both PD-1+ and PD-1- effector T cells are likely to contribute to the immune control of tumor progression. These findings highlight the predominant co-inhibitory signals delivered by HVEM upon engagement of BTLA on T cells and NK cells, placing HVEM/BTLA interaction in the spotlight as a novel immune checkpoint for the reinforcement of the anti-tumor responses in malignancies of hematopoietic origin.